Efficient Phase Retrieval via Improved Binary Amplitude Modulation Masks - Chao Yang; Cheng Xu; Hui Pang; Jun Lan; Lixin Zhao; Song Hu; Wei Yan; Xianchang Zhu (IEEE Photonics Journal)
Conventional iterative phase retrieval suffers from an inherent phase ambiguity due to limited measurement intensity. Multimodal amplitude modulation introduces physical constraints to tackle the underdetermination challenge. However, the time overhead caused by mask switching slows down the imaging speed. To increase imaging speed, we report an accelerated coded phase retrieval method by optimizing modulation masks. Compared to existing methods that require at least four patterns as inputs, the proposed method requires only three mask modulations to robustly reconstruct complex objects. The transparent pixels of the two masks partially overlap, constituting a strong constraint on the objective function. An additional random mask increases the difference between diffraction intensity patterns and ensures that the algorithm converges. The proposed method of efficient modulation using pure amplitude elements may open the door to short-wavelength high-speed complex amplitude imaging. Numerical simulations and proof-of-principle experiments have verified the feasibility of this method.